Success factors of rebranding strategy of Telekom Malaysia from the employee perspectives / Siti Anom Ahmad - Ahmad, Siti Anom (Faculty of Business and Management, 2005)
The major functions of Telekom Malaysia (TM) is to be the leader of regional information and communications group, offers a comprehensive range of communication services and solutions in fixed line, mobile, data and broadband. Therefore the objectives of this research are to determine the factors that influenced the rebranding strategy of TM several variables such the marketing mix tools (product, price, promotion and place), market dominance and competition. Two approaches of collecting data are being used. The first approach is primary data such as questionnaires while the second approach is secondary data such as TM Annual Report, Magazines, pamphlets, textbook, journals and Internet (external data). From the findings, it was concluded that majority of the respondents ( TM's staff) have agreed that product, price, promotion and place, competition and market dominance are the factors that influence the rebranding strategy. The outcome of this research is important in creating a strategy corporate image in the eyes of the customers. By determining these factors it is hoped that the customers will be more loyal and satisfied with TM services.